Advanced Corrosion Protection of Additive Manufactured Light Metals by Creating Ceramic SurfaceThrough CERANOD® Plasma Electrolytical Oxidation Process - Jantimapornkij, Patcharawee; Zerrer, Jörg; Buling, Anna (Frontiers in Chemical Engineering, 2021)
Lightweight structures produced by additive manufacturing (AM) technology such as the selectively laser melting (SLM) process enable the fabrication of 3D structures with a high degree of freedom. A printed component can be tailored to have specific properties and render possible applications for industries such as the aerospace and automotive industries. Here, AlSi10Mg is one of the alloys that is currently used for SLM processes. Although the research with the aim improving the strength of AM aluminum alloy components is rapidly progressing, corrosion protection is scarcely addressed in this field. Plasma electrolytic oxidation (PEO) is an advanced electrolytical process for surface treatment of light metals such as aluminum, magnesium, and titanium. This process produces an oxide ceramic-like layer, which is extremely hard but also ductile, and significantly improves the corrosion and wear behavior. The aim of this study is to understand the corrosion behavior of 3D-printed AlSi10Mg alloy and to improve its corrosion resistance. For this reason, the properties of CERANOD® - PEO coating on an AlSi10Mg alloy produced by SLM were investigated on different AM surfaces, i.e., as-built, polished and stress relieved specimens. The corrosion performance of these surfaces was analyzed using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, and long-term immersion tests. Moreover, the microstructure and morphology of the resulting coatings were characterized by SEM/EDS, taking into account the corrosive attacks. The results exhibited a high amount of localized corrosion in the case of the uncoated specimens, while the PEO process conducted on the aluminum AM surfaces led to enclosed homogeneous coatings by protecting the material’s pores, which are typically observed in AM process. Thereby, high corrosion protection could be achieved using PEO surfaces, suggesting that this technology is a promising candidate for unleashing the full potential of 3D light metal printing.